2004
DOI: 10.1042/bj20031143
|View full text |Cite
|
Sign up to set email alerts
|

Defining the function of xeroderma pigmentosum group F protein in psoralen interstrand cross-link-mediated DNA repair and mutagenesis

Abstract: Many commonly used drugs, such as psoralen and cisplatin, can generate a very unique type of DNA damage, namely ICL (interstrand cross-link). An ICL can severely block DNA replication and transcription and cause programmed cell death. The molecular mechanism of repairing the ICL damage has not been well established. We have studied the role of XPF (xeroderma pigmentosum group F) protein in psoralen-induced ICL-mediated DNA repair and mutagenesis. The results obtained from our mutagenesis studies revealed a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…These results suggest that the entire NER pathway is not necessary to generate DSB in cells, and that the XPF protein specifically participates in an NER-independent function that is required and probably rate-limiting for DSB formation in human cells. This conclusion is generally in agreement with prior work, which indicated that the NER functions of XPF are distinct from its role in ICL processing [23,47,48]. Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that the entire NER pathway is not necessary to generate DSB in cells, and that the XPF protein specifically participates in an NER-independent function that is required and probably rate-limiting for DSB formation in human cells. This conclusion is generally in agreement with prior work, which indicated that the NER functions of XPF are distinct from its role in ICL processing [23,47,48]. Our work in human cells corroborates and complements prior work, all in Chinese hamster ovary cells, demonstrating that ERCC1, which normally is in a heterodimeric complex with XPF, is required for the initial incisions and γ-H2AX formation [32], and that XPF and ERCC1 are required for incisions leading to DSB in an in vitro assay [14].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, XP-F (XP2YO-SV) cells stably transfected with a plasmid encoding wildtype XPF cDNA were examined. In contrast to XP-F cells which had nearly undetectable XPF protein, XPF-corrected cells expressed ~40% of the level of XPF found in control GM637 cells, as previously described [23] (Fig. 3B).…”
Section: γ-H2ax Formation Following Psoralen Icl Requires Xpfsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the unique DNA damage generated by cisplatin, ICLs, may also contribute to this ATM activation. Although the mechanism of repairing ICLs is not fully understood, it is known that NER is involved in this repair process (47)(48)(49)(50)(51)(52)(53)(54)(55). It is possible that the ICL-mediated NER process generates the DNA repair intermediates required for ATM activation, whereas the defects of XPA or XPG proteins prevent the NER process and the generation of these DNA repair intermediates.…”
Section: Discussionmentioning
confidence: 99%